Pengaruh Pengelolaan Ekonomi Produktif dalam Mengentaskan Kemiskinan di Kota Lumajang Studi pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Lumajang - Izzah Masruroh; Muhammad Farid (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
This study discusses the effect of productive economic management in the National Zakat Agency (BAZNAS) of Lumajang Regency. The formulation of the problem in this study are: 1. Does the management of the productive economy in BAZNAS Lumajang Regency affect poverty alleviation. The objectives of this study are: 1. To find out the empirical evidence of the effect of productive economic management in alleviating poverty in the city of Lumajang. This research uses quantitative methods, with a field research approach. Data collection techniques using questionnaires, interviews, observation, and documentation. The data analysis uses a simple regression statistical tool. The results of this study indicate that there is a positive and significant influence between productive economic management on poverty alleviation in Lumajang city with R2 = 0.6739, which indicates that 67.39% of poverty reduction variables can be influenced by productive zakat management variables, while 32.61 The remaining% is influenced by other variables not included in the simple regression model.